Students Difficulties in Listening Comprehension at the Junior High School - Angely Chai; Joya Jane Grenada Simanjuntak; Fachri Yunanda; Bambang Lubis (Journal of Education Research, 2026)
This study aims to analyze the types of listening comprehension difficulties experienced by junior high school students, the underlying factors contributing to these difficulties, and the strategies employed by teachers to address them. Listening plays a crucial role in English language learning as it supports learners in understanding spoken information accurately. However, many students still encounter significant challenges in listening activities. This study employed a descriptive qualitative method involving 15 eighth-grade students of SMP Swasta Asga Mandiri Medan in the 2025/2026 academic year. Data were collected through a listening test and a questionnaire, each consisting of 15 items. The findings revealed that students’ listening comprehension ability was relatively low, with a mean score of 52. The major difficulties included limited vocabulary, problems in recognizing pronunciation and different accents, lack of concentration, poor audio quality, and difficulty in understanding long sentences. These findings indicate that listening comprehension problems are complex and interrelated. Therefore, teachers need to implement more adaptive strategies, such as providing clearer audio materials, using contextualized listening activities, and strengthening vocabulary instruction systematically. The study implies that listening instruction should be designed in a structured, interactive, and needs-based manner to improve students’ learning outcomes effectively.